Differential Effect of Generalized and Abdominal Obesity on the Development and Progression of Diabetic Retinopathy in Chinese Adults With Type 2 Diabetes - Han, Xiaoyan; Wu, Huimin; Li, Youjia; Yuan, Meng; Gong, Xia; Guo, Xiao; Tan, Rongqiang; Xie, Ming; Liang, Xiaoling; Huang, Wenyong; Liu, Hua; Wang, Lanhua (Frontiers in Medicine, 2022)
Background: The relationship between obesity and diabetic retinopathy (DR) remains controversial. The aim of this study was to assess the association of generalized obesity (assessed by body mass index [BMI]) and abdominal obesity (assessed by waist to hip ratio [WHR]) with incident DR, and vision-threatening DR (VTDR), and DR progression among Chinese adults with type 2 diabetic mellitus (T2DM). Method: This prospective cohort study was conducted at the Zhongshan Ophthalmic Center, from November 2017 to December 2020. DR was assessed based on the 7-filed fundus photographs using the modified Airlie House Classification. Multivariable logistic regression models were used to evaluate the associations of BMI and WHR with the development and progression of DR after adjusting for age, sex, traditional risk factors, and mutually for BMI and WHR. Results: Among the 1370 eligible participants, 1195(87.2%) had no sign of any DR and 175(12.8%) had DR at baseline examination. During the 2 years follow-up visit, 342(28.6%) participants had incident DR, 11(0.8%) participants developed VTDR, 15 (8.6%) demonstrated DR progression. After adjusting for confounders, the BMI was negatively associated with incident DR (relative risk[RR] =0.31; 95% confidence interval [CI], 0.26-0.38; P＜0.001) and incident VTDR (RR=0.22; 95%CI, 0.11-0.43; P＜0.001), while WHR was positively associated with incident DR (RR=1.47; 95%CI, 1.27-1.71; P＜0.001). BMI and WHR level were not significantly associated with 2-year DR progression in multivariate models (all P ＞0 .05). Conclusions: This study provides longitudinal evidence that generalized obesity confer a protective effect on DR, while abdominal obesity increased the risk of DR onset in Chinese patients, indicating that abdominal obesity is a more clinically relevant risk marker of DR than generalized obesity.